Genetic resources of potatoes Ustimovka experimental station of plant production - Бондус, Р. О. (Scientific Progress & Innovations, 2012)
The results of studies on the formation and maintenance of the collection of potato crop Ustimovka experimental station (south forest-steppe of Ukraine), which consists of 615 samples from more than 30 countries. The basic directions of work, the value and importance of formation, replenishment and conservation of potato gene pool. Revealed aspects of the search for sources of agronomic traits. Arrangements were made to attract, and NIJ study of introduced material, formed by the four indicative of the collection, selected samples of the Securities agronomic traits, which-rye transferred to research institutions of Ukraine for further inclusion in breeding programs for potatoes. The use of sources of agronomic traits from a collection of potato gene pool makes it possible to create a new valuable source material for breeding.